IMPLEMENTASI LINGKUNGAN YANG AMAN DAN INKLUSIF UNTUK MELAWAN BULLYING DI SDN KEDUNG DALEM II - Nur Kholifah; Kuhrotun Nada; Ikhwan Nur Hakim; Feny Nida Fitriyani (Fakultas Tarbiyah dan Keguruan, 2025)
This study aims to identify and analyze the implementation of a safe and inclusive environment as an effort to combat bullying at Kedung Dalem II Elementary School. Bullying must be eliminated immediately because this behavior has very serious consequences both in the short and long term for its victims. In the short term, bullying can cause injuries due to physical violence, cause feelings of insecurity, fear of going to school, and feel isolated, while in the long term, it can have lifelong effects on victims, victims of bullying can suffer from emotional and behavioral disorders such as feelings of low self-esteem. Using a qualitative descriptive approach, this study explores various strategies implemented by the school, including the involvement of teachers, students, and parents in creating an anti-bullying culture. Data were collected through observation, in-depth interviews, and documentation. The results of the study indicate that the implementation of a safe and inclusive environment is carried out through strengthening the values ​​of togetherness, providing a dialogue space for students, and sensitivity training for teachers and school staff. In addition, collaboration between schools and parents plays an important role in preventing and handling bullying cases. This study concludes that an inclusiveness-based approach not only reduces bullying incidents but also increases mutual respect among students. The implications of this research can be a reference for other schools to develop a safe and inclusive learning environment.